Ions Diffusion and Electrodynamics Interactions Inside Pancreatic Beta Cells - Nieto-Chaupis, Huber (2020)
In this paper a hybrid scheme given by diffusion equation in conjunction to classical electrodynamics to examine physics-based mechanisms behind the behavior of beta cells, is presented. Particular attention is paid on the scenario by which beta-cell is not able to segregate insulin granules. Thus, a mechanism that would explain anomalies as seen in the lost of functions to segregate granules of insulin, is proposed. In this manner, the main argument of this paper states that the processes previous to the segregation of insulin given by (i) entrance of insulin, (ii) exit of Potassium K+, (iii) entrance of Calcium 2+, and (iv) segregation of insulin belong in only one universal formulation. A pseudo code by which the diabetes disease might be seen as a bug of the biological software of beta cell is proposed. Therefore a scheme capable to fix that bug would constitute a path to alleviate the disease inside the framework of Nanomedicine.